Performance of submerged membrane – Ion exchange hybrid system with Purolite A502PS in treating reverse osmosis feed - Sukanyah, S.; Nguyen, T.V.; Shim, W.G.; Kandasamy, J. (ELSEVIER, 2014)
The performance of ion exchanger Purolite A502PS in treating biologically treated sewage effluent (Reverse Osmosis feed) was evaluated in a submerged membrane ion exchange hybrid system (SMIHS). The experimental results showed that adding a small amount of Purolite A502PS of 0.5 g/L increased the organic removal of the submerged membrane reactor from less than 10% to above 40%. The homogeneous surface diffusion model (HSDM) could predict the adsorption kinetics of Purolite A502PS. A higher dose of Purolite A502PS in SMIHS led to better organic removal as well as reduced membrane resistance. After one hour of operation at a flux of 36 LMH, the amount of organic matter retained on the membrane surface decreased from 2.11E 9 kg/m2 s to 8.25E 10 kg/m2 s when 1 g/L of Purolite A502PS was added into the submerged membrane reactor. Although the increase of membrane flux from 36 L/m2 h (LMH) to 60 LMH did not have much effect on organic removal, more organics were adsorbed onto the membrane surface. This led to a higher transmembrane pressure (TMP) of 12 kPa in the SMIHS after eight hours operation at a flux 60 LMH. The increase in TMP was approximately four times higher than that at a flux of 36 LMH.
Keywords: Submerged membrane ion exchange hybrid system; Modelling; Organic; Purolite A502PS; Reverse osmosis feed